PENGGUNAAN MEDIA PREZI UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA DALAM MATERI TEKS BIOGRAFI KELAS VIII - Nurizalianto Ramadhan; Bagus Wijaya (Universitas Islam Malang, 2023)
The purpose of this study was to investigate the use of Prezi media in improving students' listening skills in biographical text material in grade VIII. Qualitative literature studies are conducted by analyzing previous studies conducted in similar contexts. The results of the literature study show that the use of Prezi media in biographical text material has various benefits. Prezi's engaging and interactive visuals help students understand and visualize the information in the biographical text better. Prezi's organized structure and navigation features make it easy for students to follow the narrative flow of the biography and track the character's character development. In addition, the use of Prezi can also increase student engagement, learning motivation, and presentation skills. The use of Prezi media in biographical text materials can improve students' listening skills. Deep understanding, better analytical skills, informed response skills, high engagement and motivation, and improved presentation skills are some of the outcomes produced.